In Focus n° 3: Sana’a and Rapid Urbanization in some Short Stories by Muḥammad al‑Gharbī ‘Amrān - Patrizia Zanelli (Arabian Humanities)
This article presents a few short stories by the famous Yemeni writer Muḥammad al‑Gharbī ‘Amrān and offers some information regarding Yemeni society to illustrate these tales set in Sana’a on the threshold of the 21st century. The author focuses on the new features of the expanding metropolis as he highlights the shortcomings of rapid urbanization, such as air pollution, landscape alteration and above all social fragmentation caused by rural‑urban migration. Combined with long standing gender and racial segregation, the recent collapse of traditional familial and communal networks leads to solitude in a populous city like Sana’a: this is the paradox that ‘Amrān highlights in most of his stories. In other tales, he focuses on poverty and especially on extreme poverty, showing how socio‑economic inequalities in Yemen have increased due to free market economy.